Addressing Cross-Sectoral Challenges in Consumer Culture for Sustainability and Social Justice in Indonesia - Erwin Erwin; Arief Fahmi Lubis; Feliks Anggia Binsar Kristian Panjaitan; Hotman Panjaitan (West Science Social and Humanities Studies, 2023)
In the context of Indonesia's dynamic socioeconomic landscape, this research focuses on sustainability and social justice while addressing cross-sectoral concerns in consumer culture. Through the use of a mixed-methods approach that incorporates qualitative interviews, quantitative surveys, and in-depth case studies, the study sheds light on the complex interactions between environmental, cultural, and economic elements that influence consumer behavior. Results highlight financial limitations by showing a relationship between sustainable practices and socioeconomic level. Traditional and global cultural influences become important, influencing motivations and creating obstacles. Consumer choices are greatly influenced by business practices, which emphasizes the importance of transparency in promoting positive change. Case studies offer practical examples that highlight both the advantages and disadvantages of consumer behavior. Actionable recommendations for businesses, consumers, and politicians are informed by the combination of quantitative and qualitative findings, paving the way for Indonesia to adopt a more socially equitable and sustainable consumption culture.